Weight loss and sexual activity in adult obese individuals: Establishing a causal link - Arndt R. Reichert; Harald Tauchmann; Ansgar Wübker (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2015)
Obesity may not only be linked to undesirable health outcomes but also to limitations in sexual life. The present paper aims to assess whether there is a causal relationship between weight loss and sexual activity in adult obese individuals. To address the endogeneity of weight loss that is likely to result in biased estimation results, the analysis is based on data from a randomized field experiment. In this experiment financial weight-loss rewards were offered to a random subgroup of participants and can be used as exogenous source of weight variation in an instrumental variables approach. Estimation results indicate that for obese males loosing weight increases the probability for being involved in a sexual relationship. Conditional on having already lost some weight, a further reduction in obesity also increases the frequency of sexual intercourse.
Keywords: I10; I18; J28; J65; 330; obesity; sexual partnership; frequency of intercourse; randomized trial; weight-loss incentives